ANALISIS PRINSIP KESANTUNAN BERBAHASA DALAM KOMENTAR NETIZEN DI MEDIA SOSIAL TIKTOK. - Abellia; Wahidy, Achmad; Puspita, Yenny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze the forms of politeness and impoliteness in netizen comments on TikTok regarding the Free Nutritious Meals program. The digital communication phenomenon on TikTok often gives rise to polarized opinions that impact people's choice of language style in the public sphere. Using a descriptive qualitative approach, the data in this study consist of excerpts of comments containing evaluative content regarding the policy. The analysis was conducted by applying Leech's politeness principle theory, which includes the maxims of wisdom, generosity, praise, humility, agreement, and sympathy. The results show that although some comments fulfill the principles of politeness as a form of support for the program, there are still many violations of politeness, dominated by the maxims of agreement and praise. This impoliteness often manifests in the form of sarcasm, sharp criticism, and the use of informal diction that tends to be provocative. Factors causing this low politeness are influenced by user anonymity, differences in political views, and skepticism towards the program's implementation mechanisms in the field. This study concludes that TikTok's comment space on public policy issues still requires more in-depth digital literacy education to create a healthier and more civilized discussion climate.